1997
DOI: 10.3109/10428199709114167
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit Point mutation in patients with myeloproliferative disorders

Abstract: Myeloproliferative disorders (MPD) constitute a group of hematopoietic neoplasms at the myeloid stem cell level. Myeloid stem cells and/or progenitor cells from MPD have been considered sensitive to hematopoietic growth factors, including erythropoietin, thrombopoietin and stem cell factor (SCF). SCF is a ligand for c-kit receptor with tyrosine kinase. We analysed the gene alteration of the c-kit extracellular domain in MPD patients by PCR-SSCP and subsequent nucleotide sequencing. The point mutation in the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…70 Mutations of c-Kit and altered c-Kit function in MPD may contribute to neoplastic clonal proliferation. 21 SCF acts synergistically with erythropoietin to support the proliferation of erythroid precursors, suggesting a possible role in the pathogenesis of PV. 24,71 Red blood cells isolated from patients with PV form erythroid burst-forming units even in the absence of erythropoetin.…”
Section: Imatinib In Mpds Pathophysiologic Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…70 Mutations of c-Kit and altered c-Kit function in MPD may contribute to neoplastic clonal proliferation. 21 SCF acts synergistically with erythropoietin to support the proliferation of erythroid precursors, suggesting a possible role in the pathogenesis of PV. 24,71 Red blood cells isolated from patients with PV form erythroid burst-forming units even in the absence of erythropoetin.…”
Section: Imatinib In Mpds Pathophysiologic Rationalementioning
confidence: 99%
“…20 Synergism between erythropoietin and several growth factors, including SCF, leads to the maturation and proliferation of erythroid precursors. [21][22][23][24] Imatinib (formerly STI571; Glivec, Gleevec; Novartis Pharmaceuticals, Basel, Switzerland) is an orally bioavailable 2-phenylaminopyrimidine compound that was designed rationally to inhibit adenosine triphosphate binding to protein-tyrosine kinases and, thus, to block the activation of kinase-mediated intracellular signal transduction pathways. 18,[25][26][27][28] These pathways control fundamental cellular processes, such as growth, metabolism, differentiation, adhesion, and apoptosis.…”
mentioning
confidence: 99%
“…Although the biology of GIST is now well understood (4), the precise incidence of GIST is unknown due to the incomplete definition and classification of the tumor (5). GIST, mastocytosis syndromes and certain types of leukemia are associated with the presence of mutations in c-kit and pdgfra genes (6)(7)(8)(9). These genes encode the KIT protein [stem cell factor (SCF) receptor] and platelet-derived growth factor receptor α (PDGFRA), which are membrane receptors with tyrosine kinase activity; both proteins are involved in essential cellular signaling pathways that promote cell growth and proliferation (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, it is well recognized that activating mutations of the c-kit gene on chromosome 4 are also found in myeloproliferative disorders (MPD). [2][3][4] In a study of 25 patients with MPD, Kimura and Nakata found point mutations in exon 2 of the c-kit extracellular domain, leading to D52N substitution in one patient with chronic myelogenous leukemia (CML) and two patients with primary myelofibrosis (PMF). The authors postulated that this mutation might affect the tertiary SCF-binding site or the efficiency of ligand-induced dimerization of the receptor leading to the enhancement of the receptor kinase activity of the intracellular domain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the D52N substitution resulted in apparently higher sensitivity of erythroid progenitor to SCF. 2,3 Using RT-PCR Inokuchi et al 4 studied 80 patients with CML in various clinical phases and identified sequence alterations in the c-kit juxtamembrane domain in seven cases. The authors concluded that these mutations led to leukocytosis (Po0.05) and to shorter survival (P ¼ 0.04) of CML patients.…”
Section: Introductionmentioning
confidence: 99%